Clinical evaluation of WT1 mRNA expression levels in peripheral blood and bone marrow in patients with myelodysplastic syndromes. Issue 7 (July 2013) - Ueda, Yasunori; Mizutani, Chisato; Nannya, Yasuhito; Kurokawa, Mineo; Kobayashi, Sumiko; Takeuchi, Jin; Tamura, Hideto; Ogata, Kiyoyuki; Dan, Kazuo; Shibayama, Hirohiko; Kanakura, Yuzuru; Niimi, Keiko; et al.
Abstract: A study to evaluate WT1 mRNA expression levels in peripheral blood (PB) and bone marrow aspirate (BM) was conducted in 172 patients, including 115 with myelodysplastic syndromes (MDS), in Japan. The level of WT1 mRNA expression was evaluated according to the French–American–British (FAB) and World Health Organization (WHO) classifications (2001, 2008) and using the International Prognostic Scoring System and the WHO Prognostic Scoring System scales. WT1 mRNA expression levels in PB and BM were well correlated ( r = 0.85), and they tended to increase with disease stage progression and in those at higher risk of leukemic transformation. WT1 mRNA expression can be a useful marker for the diagnosis and risk evaluation of MDS.